Skin‐Inspired Thermoreceptors‐Based Electronic Skin for Biomimicking Thermal Pain Reflexes. Issue 27 (25th July 2022) - Neto, João; Chirila, Radu; Dahiya, Abhishek Singh; Christou, Adamos; Shakthivel, Dhayalan; Dahiya, Ravinder
Abstract: Electronic systems possessing skin‐like morphology and functionalities (electronic skins [e‐skins]) have attracted considerable attention in recent years to provide sensory or haptic feedback in growing areas such as robotics, prosthetics, and interactive systems. However, the main focus thus far has been on the distributed pressure or force sensors. Herein a thermoreceptive e‐skin with biological systems like functionality is presented. The soft, distributed, and highly sensitive miniaturized (≈700 µm 2 ) artificial thermoreceptors (ATRs) in the e‐skin are developed using an innovative fabrication route that involves dielectrophoretic assembly of oriented vanadium pentoxide nanowires at defined locations and high‐resolution electrohydrodynamic printing. Inspired from the skin morphology, the ATRs are embedded in a thermally insulating soft nanosilica/epoxy polymeric layer and yet they exhibit excellent thermal sensitivity (−1.1 ± 0.3% °C −1 ), fast response (≈1s), exceptional stability (negligible hysteresis for >5 h operation), and mechanical durability (up to 10 000 bending and twisting loading cycles). Finally, the developed e‐skin is integrated on the fingertip of a robotic hand and a biological system like reflex is demonstrated in response to temperature stimuli via localized learning at the hardware level. Abstract : This work presents anelectronic skin (e‐skin) having distributed, miniaturized temperature sensors or thermoreceptors and a peripheral nervoussystem‐like localized learning scheme, allowing robots to mimic the thermal pain like reflexes. The vanadium pentoxide nanowires (NWs)‐based thermoreceptors are developed with dielectrophoresis approach for precise assembly and high‐resolution printing of NWs. The e‐skin exhibits excellent thermal sensitivity, fast response, and flexibility.